Possible role of DIETs in devising new curriculum - Reddy, N. Upender (Voices of Teachers and Teacher Educators, 2015)
As per the policy document Govt. of India, DIETs are the premier institutes at the district level, which look after both pre-service and in-service teacher education at the elementary level.The D.Ed. course is requiredto gear potential teachers to deal with field level challenges. The faculty of DIETsis thus familiar with ground level reality. While revising the D.Ed. curriculum in Telangana, it was felt that faculty from the DIETs and other Teacher Education Institutions (TEIs) as well as Teachers Resource Group members should be involved in the exercise so that the focus is on the gaps in the existing curriculum, both in theory and in field level practices